siRNA Knockdown of RRM2 Effectively Suppressed Pancreatic Tumor Growth Alone or Synergistically with Doxorubicin - Shuquan Zheng; Xiaoxia Wang; Yu-Hua Weng; Xingyu Jin; Jia-Li Ji; Liangxia Guo; Bo Hu; Nan Liu; Qiang Cheng; Jianqi Zhang; Huicheng Bai; Tongren Yang; et al. (Elsevier, 2018)
Pancreatic cancer is currently one of the deadliest of the solid malignancies, whose incidence and death rates are increasing consistently during the past 30 years. Ribonucleotide reductase (RR) is a rate-limiting enzyme that catalyzes the formation of deoxyribonucleotides from ribonucleotides, which are essential for DNA synthesis and replication. In this study, 23 small interfering RNAs (siRNAs) against RRM2, the second subunit of RR, were designed and screened, and one of them (termed siRRM2), with high potency and good RNase-resistant capability, was selected. Transfection of siRRM2 into PANC-1, a pancreatic cell line, dramatically repressed the formation of cell colonies by inducing remarkable cell-cycle arrest at S-phase. When combining with doxorubicin (DOX), siRRM2 improved the efficacy 4 times more than applying DOX alone, suggesting a synergistic effect of siRRM2 and DOX. Moreover, the combined application of siRRM2-loaded lipid nanoparticle and DOX significantly suppressed the tumor growth on the PANC-1 xenografted murine model. The inhibition efficiency revealed by tumor weight at the endpoint of the treatment reached more than 40%. Hence, siRRM2 effectively suppressed pancreatic tumor growth alone or synergistically with DOX. This study provides a feasible target gene, a drug-viable siRNA, and a promising therapeutic potential for the treatment of pancreatic cancer. Keywords: pancreatic cancer, RRM2, siRNA, doxorubicin, small interfering RNA, RNA interference, LNP, lipid nanoparticle, combined therapy, synergistic effect